2009
DOI: 10.1002/qua.22009
|View full text |Cite
|
Sign up to set email alerts
|

Proton affinity and enthalpy of formation of formaldehyde

Abstract: The proton affinity and the enthalpy of formation of the prototypical carbonyl, formaldehyde, have been determined by the first-principles composite focalpoint analysis (FPA) approach. The electronic structure computations employed the allelectron coupled-cluster method with up to single, double, triple, quadruple, and even pentuple excitations. In these computations the aug-cc-p(C)VXZ [X ϭ 2(D), 3(T), 4(Q), 5, and 6] correlation-consistent Gaussian basis sets for C and O were used in conjunction with the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 152 publications
(240 reference statements)
4
33
0
Order By: Relevance
“…[62,63] The CBS energies for CCSD(T) were obtained by using published formulas. [62,[64][65][66][67][68][69] Zero-point energies and thermal corrections at 298 K were added to calculate the (ROHF)MP2 and CCSD(T) BDEs. [53] 2.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[62,63] The CBS energies for CCSD(T) were obtained by using published formulas. [62,[64][65][66][67][68][69] Zero-point energies and thermal corrections at 298 K were added to calculate the (ROHF)MP2 and CCSD(T) BDEs. [53] 2.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As a result, for equivalent amounts of the parent molecules, a larger quantity of protonated molecules is obtained, thus increasing the sensitivity of detection. On the contrary, it has been shown that when the PA difference between the molecule and water is small, as for formaldehyde for instance (PA(H 2 CO)0 711.0 kJ mol − 1 ) [36], involving a difference of 20 kJ mol −1 , the back-reaction of the protonated molecule with water occurs and reduces the sensitivity [37]. As indicated in "Quantum chemistry calculation of proton affinities and proton transfer reaction rate coefficients", PA(1) is close to 880 kJ mol −1 , while PA(2) and PA(3) are close to 900 kJ mol −1 .…”
Section: Sensitivitymentioning
confidence: 97%
“…It is often not possible to fulfill all these criteria simultaneously and thus some care should be exercised when selecting the best reaction. For example, when trying to determine the enthalpy of formation of formaldehyde it is advantageous [80] to use the reaction H 2 CO = H 2 + CO over either…”
Section: Wwwchemeurjorgmentioning
confidence: 99%